2016
DOI: 10.1007/s11033-016-3959-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of molecular markers, based on chloroplast and ribosomal DNA regions, to discriminate three popular medicinal plant species, Cynanchum wilfordii, Cynanchum auriculatum, and Polygonum multiflorum

Abstract: Identification of plant species is important for standardizing herbal medicine. Cynanchum wilfordii (Baekshuoh in Korean) and Polygonum multiflorum (Hashuoh in Korean) are important oriental medicinal herbs in Korea, Japan, and China. Cynanchum auriculatum is a faster growing and more productive plant than C. wilfordii; and, it is not recognized as a medicinal plant in the Korean Pharmacopoeia. C. wilfordii, P. multiflorum, and C. auriculatum are often misidentified in the Korean herbal medicine marketplace du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Fallopia multiflora (Hashuoh in Korean) is an important herb in Korea, Japan, and China (Han et al 2016). We extracted genomic DNA from fresh leaves collected from the Oriental Medicine Resource Center of Wonkwang University (geographic coordinate: N 35 56 0 38 00 , E 126 57 0 16 00 ).…”
mentioning
confidence: 99%
“…Fallopia multiflora (Hashuoh in Korean) is an important herb in Korea, Japan, and China (Han et al 2016). We extracted genomic DNA from fresh leaves collected from the Oriental Medicine Resource Center of Wonkwang University (geographic coordinate: N 35 56 0 38 00 , E 126 57 0 16 00 ).…”
mentioning
confidence: 99%
“…HRM analysis is also a highly sensitive method for detecting SNPs, allowing sequence differences between species to be readily detected without the need for direct sequencing. ARMS-PCR and HRM analyses were recently used to discriminate among various medicinal plants, such as members of the diverse Panax genus and similar plant species Cynanchum wilfordii, C. auriculatum, and Polygonum multiflorum (Kim et al 2013;Han et al 2016). In the current study, we showed that SNPs in the MatK regions of plastid sequences and the ITS regions of nuclear sequences are effective, reliable tools for discriminating among C. tricuspidata ecotypes originating from the same country, such as Korea and China (Fig.…”
Section: Development Of a Chloroplast And Nuclear Dna-based Hrm Assaymentioning
confidence: 99%
“…Most gene sequences are also highly conserved in various plant species, but considerable amounts of nucleotide variation have been identified in chloroplast intergenic spacer regions at the interspecies level and (rarely) at the intraspecies level (Wolfe et al 2004). In addition, nuclear ribosomal DNA internal transcribed spacer (ITS) sequences have recently been used to develop molecular markers to identify various medicinal plant species originating from Korea and China (Yang et al 2012;Han et al 2016). Hybrids may also be produced via cross-fertilization when similar species or ecotypes are cultivated in the same field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Authentication of 11 collected samples of three different species, Cynanchum wilfordii, Cynanchum auriculatum, and Polygonum multiflorum (Han et al 2016).…”
mentioning
confidence: 99%